1995
DOI: 10.1148/radiology.197.3.7480766
|View full text |Cite
|
Sign up to set email alerts
|

Patellar tendinitis: MR imaging features, with suggested pathogenesis and proposed classification.

Abstract: Patellar tendinitis demonstrates a consistent spectrum of changes at MR imaging that can aid understanding of the origin and treatment of damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 0 publications
3
39
0
1
Order By: Relevance
“…Shalaby et al [15] have reported that, abnormal MRI findings might be present in asymptomatic knees of older active patients and in only Blazina stage III patients of patellar tendinitis but we have documented abnormal MRI findings in our young patient group and who were asymptomatic. McLoughlin et al [12] have classified ''jumper's knee'' with MRI findings according to the involvement of the tendon in craniocaudal plane, presence of perichondral-bone avulsion and intratendinous signal alterations. We did not use this classification system because the lesions in our case series were not characteristic for ''jumper's knee''.…”
Section: Discussionmentioning
confidence: 99%
“…Shalaby et al [15] have reported that, abnormal MRI findings might be present in asymptomatic knees of older active patients and in only Blazina stage III patients of patellar tendinitis but we have documented abnormal MRI findings in our young patient group and who were asymptomatic. McLoughlin et al [12] have classified ''jumper's knee'' with MRI findings according to the involvement of the tendon in craniocaudal plane, presence of perichondral-bone avulsion and intratendinous signal alterations. We did not use this classification system because the lesions in our case series were not characteristic for ''jumper's knee''.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the addition of the Gd-contrast agent made it possible to reveal lesions not detected on other sequences. The literature on the application of Gd CME on tendons is limited (Movin et al, 1998a, Movin et al, 1998b, McLoughlin et al, 1995. used Gd CME in patients with chronic mid-portion Achillodynia and concluded that the intratendinous signal alterations were more obvious after Gd contrast agent was used (Movin et al, 1998a) and that Gd CME depicted a larger size of the intratendinous abnormality than US (Movin et al, 1998b).…”
Section: Static and Dynamic Contrast Agent Enhancement (Studies 1-ii)mentioning
confidence: 99%
“…It is at rest that the blood fl ow has previously been measured. 9 The bone-tendon junction has traditionally been considered relatively avascular, 29 but Scapinelli 30 suggests that although the distal attachment of the patellar tendon does have an area of avascularity, the proximal attachment is surrounded by the inferior half of the patella and the infrapatellar fat pad, which are highly vascularized structures. 9 Innervation is supplied by a branch of the saphenous nerve.…”
Section: Anatomy and Pathology Of The Patellar Tendonmentioning
confidence: 99%
“…Several authors, however, report no signifi cant relationship between height or patellar-tendon length and patellar tendinopathy. 7,28,29,[37][38][39] Many authors have also tried to link muscle properties to patellar tendinopathy. Muscle fl exibility, muscle strength, and muscle imbalances have all been suggested as potential factors in patellar tendinopathy.…”
Section: Intrinsic Factorsmentioning
confidence: 99%
See 1 more Smart Citation